2021
DOI: 10.13057/biodiv/d220243
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of multidrug-resistant Salmonella spp. recovered from aquatic environment of Banda Aceh, Indonesia

Abstract: Abstract. Suhartono S, Ismail YS, Aini Z. 2021. Distribution of multidrug-resistant Salmonella spp. recovered from aquatic environment of Banda Aceh, Indonesia. Biodiversitas 22: 881-886. The occurrence of pathogenic bacteria in an aquatic system might increase waterborne infections including salmonellosis. This might raise a concern related to the increasing pathogenic bacteria, including the multidrug-resistant Salmonella spp. in the two major rivers, namely Lamnyong and Krueng Aceh crossing the city of Band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The following antimicrobial disk (Oxoid) were used: amoxicillin (25 μg), ampicillin (30 μg), penicillin (10 μg), nalidixic acid (30 μg), ofloxacin (5 μg), ciprofloxacin (5 μg), gentamicin (10 μg), kanamycin (30 μg), streptomycin (10 μg), azithromycin (15 μg), tetracycline (30 μg), and chloramphenicol (30 μg) were placed on the plates. Finally, plates were incubated at 37°C for 24 hours (Suhartono et al 2021).…”
Section: Resistance Analysis Of E Coli Isolatesmentioning
confidence: 99%
“…The following antimicrobial disk (Oxoid) were used: amoxicillin (25 μg), ampicillin (30 μg), penicillin (10 μg), nalidixic acid (30 μg), ofloxacin (5 μg), ciprofloxacin (5 μg), gentamicin (10 μg), kanamycin (30 μg), streptomycin (10 μg), azithromycin (15 μg), tetracycline (30 μg), and chloramphenicol (30 μg) were placed on the plates. Finally, plates were incubated at 37°C for 24 hours (Suhartono et al 2021).…”
Section: Resistance Analysis Of E Coli Isolatesmentioning
confidence: 99%
“…Reports on resistant bacteria are still very limited in Indonesia. Verawaty et al (2020) reported the presence of E. coli that is resistant to ampicillin, tobramycin, and tetracycline in the waters of Palembang, meanwhile Suhartono et al (2021) reported the presence of Salmonella spp. that are resistant to azithromycin, tetracycline, and streptomycin in the Lamnyong and Krueng waters, Aceh.…”
Section: Introductionmentioning
confidence: 99%